The Effect Of Transformational Leadership and Physical Work Environment On Performance PNPN Employee - Edo Prihania Januardo Basyir; Nancy Yusnita; Yayan Hadiyat (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research was conducted to determine the effect of transformational leadership and the physical work environment on the performance of PNPN employees with motivation as an intervening variable in land offices throughout West Priangan (Cianjur Regency, Sukabumi Regency and Sukabumi City). It is hoped that this research can provide input for institutions in improving the quality and quantity of Transformational Leadership, Physical Work Environment and Motivation, in order to improve employee performance. In this research, sampling was used using Simple Random Sampling by distributing questionnaires to 113 ASN employees at the West Priangan Land Office in 2024. Data from the questionnaire were analyzed using SPSS Version 27 and Lisrel 8.80 software. The results of this research state that Transformational Leadership influences Employee Performance, the Physical Work Environment influences Employee Performance, Motivation influences Employee Performance, Motivation is able to mediate the influence of Transformational Leadership on Employee Performance, as well as the Physical Work Environment, Motivation can still mediate its influence on Employee Performance.